BENCHMARKING: AN IMPORTANT TOOL FOR COMPETITIVENESS IN THE HANDICRAFT SECTOR - Nuciteli, Samanta Tatiane; Malagolli, Guilherme Augusto (Revista Interface Tecnológica, 2020)
Handicrafts are an economically relevant activity, representing up to 3% of GDP according to the IBGE (MDIC, 2020). However, handicrafts face an increasingly intense competition from industrialized products, which gain in scale of production and reduce costs. In search of innovation, artisans may have an important strategy for competitiveness in Benchmarking. The purpose of this article is to present a brief study on Benchmarking as a competitive strategy for handicraft products. The research methodology included a bibliographic review about the concept and process of Benchmarking, as well as a field research with artisans from the city of Monte Alto and information from official public institutions, linked to the promotion of the craft activity in the state of São Paulo.
Keywords: Benchmark; Competitiveness; Handicrafts; innovation